Propuesta de plan de mantenimiento preventivo para el mejoramiento de la línea de envasado de la empresa Cemex - Gil Rios, Luis Eduardo; Lozano Paredes, Luis Felipe (Universidad Antonio Nariño, 2024)
The central objective of this project was the design of a preventive maintenance plan for the packaging machines of the CEMEX company at the Caracolito plant located in Payande, municipality of Tolima. It arose from the need to reduce the number of failures that machines present and increase the mechanical availability of equipment classified as critical or moderately critical